2012
DOI: 10.1111/j.1742-4658.2012.08565.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of the PRL phosphatases

Abstract: The phosphatases of regenerating liver (PRLs) are an intriguing family of dual specificity phosphatases due to their oncogenicity. The three members are small, single domain enzymes. We provide an overview of the phosphatases of regenerating liver, compare them to related phosphatases, and review recent reports about each phosphatase. Finally, we discuss similarities and differences between the phosphatases of regenerating liver, focusing on their molecular mechanisms and signalling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
160
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(166 citation statements)
references
References 120 publications
(333 reference statements)
6
160
0
Order By: Relevance
“…We noticed the presence of a weak signal at a slightly lower molecular weight than PRL1, which similarly disappeared after H 2 O 2 stimulation. We speculated that this signal represents endogenous PRL2 because the molecular mass of PRL2 is slightly smaller than that of PRL1 (2). Indeed, the mobility of ectopically expressed PRL2 (without any tags) was identical to the detected signal (Fig.…”
Section: Sensitive Oxidation Of Prl By H 2 O 2 -mentioning
confidence: 66%
See 2 more Smart Citations
“…We noticed the presence of a weak signal at a slightly lower molecular weight than PRL1, which similarly disappeared after H 2 O 2 stimulation. We speculated that this signal represents endogenous PRL2 because the molecular mass of PRL2 is slightly smaller than that of PRL1 (2). Indeed, the mobility of ectopically expressed PRL2 (without any tags) was identical to the detected signal (Fig.…”
Section: Sensitive Oxidation Of Prl By H 2 O 2 -mentioning
confidence: 66%
“…The PRL 2 family is a unique subfamily of protein-tyrosine phosphatases; it consists of three homologous members (PRL1-PRL3), which have a high degree (Ͼ75%) of amino acid sequence identity. PRLs are the only protein-tyrosine phosphatases known to have a C-terminal CAAX motif, which anchors PRLs to the plasma membrane by prenylation (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, biochemical analyses using cultured cells have suggested that PRL can affect several signaling pathways involved in the regulation of cell proliferation, including mammalian/mechanistic target of rapamycin (mTOR) (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…First, we characterize the biochemical activity of this Leishmania phosphatase, which we named LmPRL-1 due to its similarity to the family of mammalian phosphatases of the regenerating liver (PRLs). PRLs are thought to participate in the control of various cellular processes, such as proliferation, differentiation, and motility (42). Second, we provide evidence that the LmPRL-1 phosphatase can be secreted during infection of macrophages and that it contributes to the survival of the parasite in these host cells.…”
mentioning
confidence: 85%